A comparison of component structures for the Australian inventory of family strengths (AIFS) between an Australian and Malaysian sample - Krauss, Steven Eric; Baharudin, Rozumah; Arshat, Zarinah; Shahrimin, Mohd. Ibrani; Juhari, Rumaya; Yaacob, Siti Nor (University of Toronto, 2007)
Formal research on family strengths in the Southeast Asian region outside of Australia is scant. Specifically, no known family strengths measures have been developed or adapted for the purpose of measuring family strengths in Malaysia. In the present study, exploratory component analysis (Gorsuch, 1997) was used to compare the component structures of the Australian Inventory of Family Strengths (AIFS) scale for a rural population of Malay families from Malaysia (n = 200), and those from the original Australian sample (n = 605) as reported in the Australian Family Strengths Research Project (Geggie et al., 2000). Initial findings from principal component analysis with varimax (orthogonal) rotation indicated similar but not identical primary component structures for both samples. Upon further analysis, correlation results indicated that the factor components of the Australian sample did not replicate particularly well for the Malaysian sample, with only one out of four components demonstrating a significant level of invariance. For further research, the authors suggest a Malaysian version of the AIFS to be developed along the same Unes as the Australian version of the instrument, i.e., by first using focus group data with Malaysian families to determine the specific constructs of strong families specific to the Malaysian cultural context.